STRUCTURAL FUNDAMENTALS OF FINANCIAL STATEMENTS. - Greer, Howard C. (The Accounting Review, 1943)
Abstract This article focuses on the structural fundamentals of financial statements. Financial analysis sometimes goes astray in assuming that the balance sheet at the year-end represents the average condition prevailing throughout the year, a condition which in some respects is usually not the case. An average balance sheet for the entire year would provide a better basis of comparison. Consistent treatment of the various classes of elements in all financial statements would soon lead even the casual reader to a better appreciation of the basic financial aspects of business activities and their results. The primary relationship expressed in accounts is that of equality. Entries are equations, ledgers "balance." Accounting starts, then, with the primary proposition that this equals that. Naturally many accounting statements stress this feature of "equality of factors." In the balance sheet attention is directed to the fact that property is equaled by ownership. A cash statement may show that the opening balance plus receipts equals disbursements plus the closing balance.